Relações públicas e mediação de conflitos organizacionais: conexões entre a Teoria da Função Política e o Manual de Mediação do Conselho Nacional de Justiça - Balbinot, Valmíria Antonia (2024)
The thesis explores the intersection between Public Relations and Organizational Conflict Mediation, based on the Judicial Mediation Manual of the National Council of Justice (CNJ) and the Political Function proposed by Roberto José Porto Simões. The study is based on the author's experience as a judicial mediator and aims to investigate to what extent the practices and elements present in the 2016 CNJ Judicial Mediation Manual can contribute to the political function of the Public Relations profession, according to the theory of Roberto José Porto Simões. Using content analysis as a method, anchored in Fossá (2003) and Bardin (2016), the research identifies and establishes connections, convergences and divergences between the CNJ principles and Public Relations practices. The conclusion points out that although Public Relations is often associated with conflict management and the balance between organizational and public interests, mediation is not yet systematized as a structured tool within the profession. The research findings confirm that the political function of Public Relations (Simões, 1995) is aligned with the principles of Judicial Mediation (CNJ, 2016), especially with regard to the search for sustainable consensus. Thus, the methodological approach demonstrates the relevance of mediation as a strategic pillar of Public Relations, as well as its applicability in diverse organizational contexts, promoting more ethical, transparent and dialogue-oriented management. The research also reinforces that the principles, strategies and instruments presented in the CNJ Judicial Mediation Manual (2016) can be incorporated into the systematization of conflict mediation in the field of Public Relations, contributing to the expansion of the scope of the profession and its impact on organizational management.